Sistem Informasi Data Pasien untuk Pengelolaan dan Monitoring Kesehatan - Asrizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The Patient Data Information System is designed to streamline the management and monitoring of patient health records. This system provides a user-friendly interface for healthcare providers to input, update, and access patient information efficiently. It allows for the secure storage and retrieval of patient data, including medical history, treatment plans, and appointment schedules. By incorporating features such as real-time data access, automated reminders for follow-up appointments, and comprehensive reporting, the system enhances the quality of patient care and operational efficiency. Additionally, the system includes tools for data analytics, enabling healthcare administrators to make informed decisions based on up-to-date patient information. The system also supports integration with other healthcare management platforms, ensuring seamless coordination across different departments and facilities. Overall, the Patient Data Information System aims to improve patient care by providing accurate and timely information to healthcare providers, thereby enhancing the overall healthcare delivery process.